2019
DOI: 10.21203/rs.2.15572/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of alternate-day fasting on body weight and dyslipidaemia in patients with non-alcoholic fatty liver disease: a randomised controlled trial

Abstract: Background: Alternate-day fasting (ADF) is a novel diet therapy that may achieve reduction in body weight and improvement of dyslipidaemia, but the impact of this diet on patients with non-alcoholic fatty liver disease (NAFLD) remains unknown. The aim of this study was to evaluate the effects of ADF on the body weight and lipid profile of individuals with NAFLD. Methods: NAFLD patients (n=271) were randomised to the ADF group, time-restricted feeding (TRF) group, or the control group and subjected to the respe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…Beneficial modulations in TG were observed by both diets. Reductions in plasma TG by ICR found in our study are consistent with those reported by several other investigators [25,29,30] but they differ from other reports of no change [31]. We also show that changes in plasma TG concentrations were correlated to changes in body weight.…”
Section: Discussionsupporting
confidence: 89%
“…Beneficial modulations in TG were observed by both diets. Reductions in plasma TG by ICR found in our study are consistent with those reported by several other investigators [25,29,30] but they differ from other reports of no change [31]. We also show that changes in plasma TG concentrations were correlated to changes in body weight.…”
Section: Discussionsupporting
confidence: 89%
“…28 A larger trial comparing alternate-day and time-restricted feeding with a control group for 12 weeks revealed that both diets led to significant short-term reductions in weight and improvements in dyslipidaemia, although no changes were seen for fasting levels of insulin or liver stiffness. 29…”
Section: Randomized Controlled Trial Datamentioning
confidence: 99%
“…Previous studies have shown that 4-12 wk of ADF administration can effectively decrease body weight and visceral fat mass (50)(51)(52). The beneficial findings for blood lipids (decrease in LDL cholesterol and triglycerides, increase in size particle of LDL) have been reported in addition to these favorable effects of ADF and Ramadan Fasting (RF) on body composition (53)(54)(55)(56).…”
Section: Nutritional Strategy In the Treatment Of The Nafld Fastingmentioning
confidence: 99%